Implementing Controlled Composition to Improve Vocabulary Mastery of EFL Students - Juriah, Juriah (Dinamika Ilmu: Jurnal Pendidikan, 2015)
The purposes of this study was to know how (1) Controlled composition teaching techniques implemented by the English teacher at SDN 027 Samarinda to improve vocabulary mastery, and (2) Controlled composition teaching techniques improves vocabulary mastery of the sixth grade students of SDN 027 Samarinda. This research used a Classroom Action Research (CAR) as the research design. The subject of the research is the sixth grade students in the 2013/2014 academic year that consists of 43 students. The instruments employed in this study were observation checklist, field note, and vocabulary test. The result of the research showed that in cycle 1 the students’ achievement did not fulfill the minimal criteria of success. However the result of the cycle 1 was better than the preliminary study. The criteria of success did not fulfill in cycle one, some enhancement of the implementation of Controlled Composition were made in cycle two in the form of: Instruct the students bring dictionary, give more examples English sentences, guide the students find the mining of words in the dictionary and write a paragraph, more motivate the students and preparing a media/ picture .Meanwhile the students ’achievement in cycle two showed that fulfilled the criteria of success. Based on the findings and discussion, the conclusions : Firstly, Controlled composition was implemented well by the teacher of SDN 027 Samarinda. Controlled composition was implemented and gave impacts in: (a) increasing the students’ vocabulary mastery significantly, (b) making the students able to spell the vocabularies, (c) making the students understand the meaning English words, and (d) making the students able to pronounce English words quite good. Secondly, Controlled composition improved the students’ vocabulary mastery; it was only 20.9% of the students who achieved the English passing grade in the preliminary study, but then 81.39% of the students achieved the English passing grade in the end of cycle 2.